Design of Risk Management System on Material Handling Services to Fulfill ISO 9001:2015 Requirements Clause 6.1 Based on ISO 31000:2018 - Qinthara, Hasya; Sutari, Wiyono; Salma, Sheila Amalia (Journal Knowledge Industrial Engineering (JKIE), 2021)
The main task in the IHKP division is to deliver goods in the form of materials, semi-finished products, finished products, or even waste, from plant A to plant B in the consumer factory area, namely the PT XYZ factory. Based on the Traffic Accident Data from the IHKP Division, there were 18 major accidents that occurred in 2016-2020. In solving the above problems, the IHKP division carries out risk management only after the risk occurs. The IHKP Division does not yet have an effective risk prevention plan. In other words, the aim of this study was to design the system of risk management for the company's material handling services to meet the requirements of ISO 9001:2015 based on ISO 31000:2018. In the first stage of the study, researchers conducted a gap analysis of the actual condition of the company and its requirements. In the second stage, the researcher makes a proposed business process design according to the gaps obtained. In the third stage, a business process improvement method was applied by the researchers to the proposed business. As a result, the proposed business process and the draft SOP are then verified to the company to ensure whether the proposal is in accordance with the company or not.